Correlation between birth weight and placental weight in healthy and diabetic puerperae - Fulvia Gloria-Bottini; Anna Neri; Luca Coppeta; Andrea Magrini; Egidio Bottini (Elsevier, 2016)
Objective: The birth weight/placental weight ratio has an important predictive value for perinatal mortality and morbidity and for cardiovascular diseases in adult life. In this study, we compared the birth weight/placental weight (BW/PW) ratio and the correlation between the two parameters in diabetic women with that observed in healthy women. Materials and Methods: A total of 347 consecutive newborn infants from healthy puerperae, 164 newborns from puerperae with gestational diabetes, 148 newborns from puerperae with preexisting type 1 diabetes, and 40 newborns from puerperae with preexisting type 2 diabetes have been studied from the White population of Rome. The research project was approved by the Institutional Review Board and informed written consent was obtained from the participating mothers. Results: The BW/PW ratio is higher, and the correlation between the two parameters is lower in all classes of diabetes as compared to healthy puerperae. A remarkably low correlation is observed in preexisting diabetes pointing to a dissociation of fetal growth from placental growth. Discussion: In diabetic pregnancy the BW/PW ratio is higher, and the correlation between birth weight and placental weight is lower in all classes of diabetic as compared to healthy puerperae pointing to a relative dissociation between the two parameters. It has been suggested that the increase of glycemic levels in diabetic pregnancy predisposes to important diseases in adult life. The dissociation of BW from PW in infants of diabetic pregnancy could be a predictor of the risk for such diseases of adult life.